Optimization Design of Structure Parameter of Wheel Hub Reducer based on PXI - Liu Qing; Wu Qibin (Jixie chuandong)
The planetary wheel hub reducer has large transmission ratio,compact structure and strong carrying capacity. Based on the structural characteristics of the secondary planetary wheel hub reducer,the number of teeth,modulus and tooth width are used as design variables under the condition of keeping the total gear ratio unchanged. Under the condition of the same input power and rotational speed,and root bending strength reaches a certain safety factor,the optimal variables are sought to minimize the overall power loss. Based on Simulink,the model of the optimal solution of the wheel-rim reducer is built and imported into Labview. The real-time simulation of the model is carried out in Labview and PXI environment and its dynamic characteristics are analyzed. The result shows,after optimization,the system power loss rate is reduced from 3. 87% to 3. 31%. The meshing deformation of gear transmission at each stage of rear wheel reducer is chaotic,the meshing deformation of gear pair is determined by the torque transmitted,and the time-dependent stiffness of gear meshing fluctuates around the stable value,which shows that the optimal design is reliable.